Implementation of student’s worksheet based on project based learning (pjbl) to foster student’s creativity - Sahtoni Sahtoni; Agus Suyatna; Posman Manurung (Universitas Sebelas Maret, 2017)
This study aimed to foster student creativity through the use of student worksheet based on Project Base Learning (PjBL) on dynamic electrical material in making alternative power sources. The research method is using a pre-experimental design with One-Shot case study type. The study population was students of class IX MTs Al-Islah in Pesawaran Lampung. A sample of one class consisting of 30 people was obtained by purposive sumpling. Data analysis was done by using descriptive concerning creativity, product, and response of students to see effectiveness of learning. The results showed that the application of student worksheet based on project based learning is overall effective to foster creativity of student. Based on the average of student’s creativity, the result is 80% which categorized as “creative.” Based on the average of student’s product, the result is 76.2% which categorized as “valuable.” The student’s response is positive as much as 92% which categorized as “very agree.”